Guidelines for the internal and external students’ self-study in International Entrepreneurship course - Zubkova, Alina (National Technical University "Kharkiv Polytechnic Institute", 2022)
Guidelines for the internal and external students’ self-study in the International Entrepreneurship course for Master of Science in 07307 International Business
Keywords: international entrepreneurship; guidelines; self-study; international business; business model; startup; management